2013
DOI: 10.1074/jbc.m113.477216
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Androgen Deprivation Therapies with Anti-androgens Casodex/Bicalutamide or MDV3100/Enzalutamide versus Anti-androgen Receptor ASC-J9® Lead to Promotion versus Suppression of Prostate Cancer Metastasis

Abstract: Background: Androgen deprivation therapy (ADT) suppresses prostate cancer (PCa) growth, yet its effects on PCa metastasis remain unclear. Results: ADT with MDV3100/enzalutamide or Casodex/bicalutamide versus ASC-J9 led to enhanced versus suppressed PCa metastasis. Conclusion: Casodex/MDV3100 induces PCa metastasis via modulation of TGF-␤1/Smad3/MMP9 signaling. Significance: Targeting androgen receptor with ASC-J9 is better than targeting androgens with Casodex/MDV3100 to better battle PCa metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 43 publications
9
91
0
Order By: Relevance
“…1C), PKC phosphorylation, and Twist1 protein expression, which was accompanied by a decreased E-cadherin and an increased fibronectin expression (Fig. 1D), consistently with the previous reports on EMT promotion by enzalutamide (27,28).…”
Section: Blocking Ar Signaling Induces Pkc Phosphorylation and Twist1supporting
confidence: 78%
“…1C), PKC phosphorylation, and Twist1 protein expression, which was accompanied by a decreased E-cadherin and an increased fibronectin expression (Fig. 1D), consistently with the previous reports on EMT promotion by enzalutamide (27,28).…”
Section: Blocking Ar Signaling Induces Pkc Phosphorylation and Twist1supporting
confidence: 78%
“…This notion is supported by previous studies that 22Rv1 cells are less dependent on AR, and the truncated AR isoforms can drive castrationresistant growth in these cells when AR is knocked down (59,60). Interestingly, a recent study showed that the anti-androgens targeting the AR ligand binding domain promotes tumor metastasis via increasing TGF␤ expression whereas the anti-AR N-terminal drug ASC-J9 inhibits tumor metastasis (61). ASC-J9 has been shown to inhibit AR3 activity in a number of prostate cancer cells (59).…”
Section: Discussionsupporting
confidence: 68%
“…Such metastasis-blocking effects are reversed by TGF-b-induced EMT, indicating a crosstalk between EMT effectors and MMP-9 in prostate tumor progression to metastasis. Moreover, clinically used first and second generation anti-androgens, Casodex or MDV3100 (enzalutamide), suppress prostate cancer cell growth yet promote prostate cancer cell invasion by activating the TGF-b1/ SMAD3/MMP9 pathway [55]. A newly developed anti-AR compound, ASC-J9, produces anti-invasion effects against prostate cancer by down-regulating MMP9 expression [55].…”
Section: Landscape Design By Tgf-b: Epithelialemesenchymal Transitionmentioning
confidence: 99%
“…Moreover, clinically used first and second generation anti-androgens, Casodex or MDV3100 (enzalutamide), suppress prostate cancer cell growth yet promote prostate cancer cell invasion by activating the TGF-b1/ SMAD3/MMP9 pathway [55]. A newly developed anti-AR compound, ASC-J9, produces anti-invasion effects against prostate cancer by down-regulating MMP9 expression [55]. Endothelial cell-induced prostate cancer invasion can be functionally prevented by blocking the IL-6/AR/TGF-b/ MMP-9 signaling pathway [56].…”
Section: Landscape Design By Tgf-b: Epithelialemesenchymal Transitionmentioning
confidence: 99%